Post-Pandemic of Covid-19 and the Need for Transforming Education 5.0 in Afghanistan Higher Education - Mohammad Naim Rahim (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
The study is aimed to lead the global educational transformation in Afghanistan to prepare higher education institutions for the post-pandemic of Covid-19. Today, the purpose of education has changed. Everything is just a click away; One can google the right answer. Therefore, there is an urgent need for redefining the national educational objectives and set new goals that are aligned with the new norms. The 21st-century learners are involved in an education that cooperates with their head, hearth, and hands. Thus, students should learn how to love, to be kind, and of course, to believe that the world is a joint home of all the creatures. To prepare learners with this global module of education, the study applied a qualitative approach using critical document analysis to establish an authentic understanding of the on-going paradigm-shift and provide practical potentials for Education 5.0 transformation. As a result, there are three categories of skills, namely learning skills, literacy skills, and life skills which help educational institutions to evolve towards the education 0.5. This article contributes to the post-pandemic educational settings in Afghanistan.